Administering DVT Prophylaxis Sooner Than 48 Hours Does Not Increase Failure of Nonoperative Management of High-Grade (Grades III-V) Splenic Injuries. Issue 4 (April 2021) - Griffard, Jared; Sappington, Bethany; Griffard, Megan; Bollig, Reagan; McMillen, James; McKinney, Amanda; Smith, Lou; Daley, Brian
Splenic injuries are mostly treated with nonoperative management (NOM) with observation to monitor for continued hemorrhage and holding early chemical DVT prophylaxis to reduce the risk of NOM failure. Eberle et al demonstrated chemoprophylaxis prior to 72 hours didn't increase failure rate of NOM. We chose to extrapolate this finding and compare outcomes in high-grade splenic injuries (HGSI) with chemoprophylaxis before and after 48 hours. From January 2013 to December 2017, 104 patients with HGSI received chemoprophylaxis with unfractionated heparin (UH) or low molecular weight heparin (LMWH) within 72 hours of diagnosis. Of these, 8 patients received chemoprophylaxis within 24 hours, 46 between 24 and 48 hours, and 50 patients between 48 and 72 hours. This population consisted of 70 males and 34 females, with an average age of 40.1 years. The average ISS was 23 and the majority (77%) were grade 3 injuries. We observed 6 failures of NOM: 1 in the <24 hour group, 3 in the 24-48 hour group, and 2 in the 48-72 hour group. There was no statistically significant difference between the <24 hour and >24 groups or between the <48 hour and 48-72 hour groups. A linear regression analysis created a model describing the time to initiation of DVT prophylaxis using age, sex, splenic injury grade, and ISS; the failure rate decreased by 0.00002% for each hour prior to giving DVT prophylaxis, with a P value of .111. We conclude a noninferiority statement that DVT prophylaxis prior to 48 hours does not increase the risk of NOM failure.